2022
DOI: 10.5964/ejop.1531
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and psychological well-being among immigrants living in Greece: Separation as mediator and interdependence as moderator

Abstract: The present study was based on the rejection-identification model regarding migrants acculturation. Personal perceived discrimination, acculturation attitudes, self-construal, and psychological well-being were examined simultaneously in Albanian and Indian immigrants residing in Greece (N = 233). It was hypothesized that perceived discrimination would be related negatively to immigrants’ psychological well-being, both directly and indirectly. A positive relationship was expected between perceived discriminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…For example, Kafetsios [56], after modelling 165 participants' self-construal with their emotions in everyday social interactions, found that people who had a greater chronic interdependent self-construal tended to reckon lower personal positive emotion levels were beneficial for a higher social interaction quality. Another study, which examined Albanian and Indian immigrants residing in Greece, revealed that immigrants with higher levels of interdependence were inclined to reduce their feelings of depression by joining in with in-group members, although this action could increase their separation from the host country [57].…”
Section: International Teachers' Emotional Acculturation and Well-beingmentioning
confidence: 99%
“…For example, Kafetsios [56], after modelling 165 participants' self-construal with their emotions in everyday social interactions, found that people who had a greater chronic interdependent self-construal tended to reckon lower personal positive emotion levels were beneficial for a higher social interaction quality. Another study, which examined Albanian and Indian immigrants residing in Greece, revealed that immigrants with higher levels of interdependence were inclined to reduce their feelings of depression by joining in with in-group members, although this action could increase their separation from the host country [57].…”
Section: International Teachers' Emotional Acculturation and Well-beingmentioning
confidence: 99%